Photoswitching hydrazones based on benzoylpyridine. Issue 44 (4th November 2019) - Mravec, Bernard; Filo, Juraj; Csicsai, Klaudia; Garaj, Vladimír; Kemka, Miroslav; Marini, Anna; Mantero, Mariachiara; Bianco, Andrea; Cigáň, Marek
Abstract : The photoswitching behaviour of three readily accesible benzoylpyridine hydrazones, whose photochromic properties depend on the benzoyl substituent and intermolecular interactions, was investigated. Abstract : The photoswitching properties of three readily accesible benzoylpyridine hydrazones were investigated. Interestingly, replacing classical stirring with ultrasound wave activation results in pure thermodynamically less stable E isomer crystallization at room temperature. The studied benzoylpyridine hydrazones exhibit both P- and T-photochromic behaviour, depending on the benzoyl substituent, and improved addressability compared to most of the previously published pyridyl based hydrazones and 2-pyridylcarboxaldehyde acylhydrazones. Low activation entropy and calculated transition state geometry favour the inversion mechanism of their thermal isomerization rather than tautomerization followed by rotation recently found for pyridyl-hydrazone ester or nitrile rotary switches. The association behaviour of the nitro derivative during its thermal E -to- Z isomerization in highly polar DMSO indicates an important role of intermolecular hydrogen bonding in the thermal kinetics of benzoylpyridine-based hydrazone photoswitches. Moreover, the addition of triethylamine significantly accelerates the rate of Z -isomer thermal isomerization from days to seconds and could thus pave the way to fast pyridyl hydrazone T-type photochromic compounds in polar solvents. This study could therefore contribute to general knowledge related to the photochromic behaviour of hydrazones as an important class of modern photoswitches.